Neuroprotection in Animal Models of Global Cerebral Ischemia - Cervantes, Miguel; González-Burgos, Ignacio; Letechipía-Vallejo, Graciela; Olvera-Cortés, María Esther; Moralí, Gabriela (IntechOpen, 2012)
None